Economics and Modern Warfare The Invisible Fist of the Market - Taillard, Michael (Springer International Publishing, 2018)
This book demonstrates how economic tools have been used throughout history to accomplish goals of military conflict, how they can be used more effectively than traditional means of warfare in the modern era, and how we can derive a better understanding of economic strategy applicable not just to the military but also to market competition. This new edition includes a thorough updating of chapters on advances in our understanding of economic warfare and more recent examples, such as ISIS's reliance on obtaining control over oil production facilities, North Korea's nuclear program, and China's emphasis on scientific research and technological innovation. This edition also features an entirely new chapter on the commercialization of the conflict over the region of Kashmir. .